The Use of Aquatic Plants in Sewage Treatment/ Using Lily of the Nile in the City of Mosul - A. Basheer, Fatimah; A.Al Masri, Naufal (Iraqi Journal of Science, 2023)
The sewage water is the main sources of pollution for the Tigris river for that reason this study was done,The ability of nature treatment were examined along the path of alkarazi valley which was covered with reed plant also the phytoremidation were examined at the establish unit(surface flow system) which was vegetative with the plant Eichhornia crassipes .The result shows that elements which can be removed by precipitation efficiency removal like turbidity where its removal percentage at the unit of treatment reached 95.2 %where the percentage of removal through the Alkarazi was 50.4%.The removal percentage of E.coli at the unit was 90.2% where the percentage of removal through the Alkarazi was 52%.The biological oxygen demand removal at the unit was 76.5% but at the pathway of alkarazi was 20.4% The removal percentage of the nutrients were too low for both of them because the biological processes became very slow during the cold seasons of the year.